2022
DOI: 10.1186/s40001-022-00746-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of Sirtuin 1 in the pathophysiology of polycystic ovary syndrome

Abstract: Polycystic ovarian syndrome (PCOS) is the most common multifactor heterogeneous endocrine and metabolic disease in women of childbearing age. PCOS is a group of clinical syndromes characterized by reproductive disorders, metabolic disorders, and mental health problems that seriously impact the physical and mental health of patients. At present, new studies suggest that human evolution leads to the body changes and the surrounding environment mismatch adaptation, but the understanding of the disease is still in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…AMPK activation significantly upregulates NAMPT expression, which enhances SIRT1 activity [ 58 ]. The AMPK-SIRT1 pathway enhances oocyte and embryo quality through anti-inflammatory, anti-apoptotic, and antioxidant effects [ 59 , 60 ]. The co-occurrence of hyperandrogenemia and hyperinsulinemia is one of the major causes of metabolic problems such as insulin resistance in PCOS.…”
Section: Effects Of Nad + and Its Precursors On Re...mentioning
confidence: 99%
“…AMPK activation significantly upregulates NAMPT expression, which enhances SIRT1 activity [ 58 ]. The AMPK-SIRT1 pathway enhances oocyte and embryo quality through anti-inflammatory, anti-apoptotic, and antioxidant effects [ 59 , 60 ]. The co-occurrence of hyperandrogenemia and hyperinsulinemia is one of the major causes of metabolic problems such as insulin resistance in PCOS.…”
Section: Effects Of Nad + and Its Precursors On Re...mentioning
confidence: 99%
“…The said data should be interpreted with caution owing to the fact that primordial follicles are formed before birth in humans, but after birth in rodents wherein the experiments were done. The Sirtuin (SIRT1) is an epigenetic inhibitor which can influence the process of germ cell loss (Wu et al., 2022). SIRT1 has a key role in controlling autophagy and hence in reduction of germ cell.…”
Section: Stages Of Oocytes Maturation In Pcos and Impact Of Autophagymentioning
confidence: 99%
“…SIRT1 is an NAD + -dependent deacetylase that acts as an intracellular regulator of transcriptional activity and various protein functions. 22 The protective effect of SIRT1 has been demonstrated in a variety of pathological conditions, including atherosclerosis, 23 neurodegenerative diseases, 24 and cerebral ischemia. 25 Past studies showed that SIRT1 exacerbated pressure overload-induced hypertrophic heart failure by modulating the metabolism of energy.…”
Section: Dhk Modulated Infantile Pneumonia Via Sirt1/ Nf-κb Pathwaymentioning
confidence: 99%